Temperature fine structure near the sea-ice margin of the Chukchi Sea - Paquette, Robert G; Bourke, Robert H. (Monterey, California. Naval Postgraduate School, 1979)
Temperature fine structure with peak-to-peak fluctuations often exceeding 2°C is prevalent throughout the marginal sea-ice zone of the shallow Chukchi Sea in midsummer. It is normally found within 20-35 km outside of the ice and seldom farther than 5-10 km inside the ice margin. It has also been infrequently found more than 100 km south of the ice. Temperature and salinity fronts of all degrees of sharpness occur in the same general area, but the two types need not be coincident. Considerable variability in time and length scales of fine structure elements has been noted with persistences ranging from 2 hours or less to more than 20 hours and length scales ranging from 600 m to more than 20 km. While much of this variability is intrinsic, part can be accounted for by the inability to sample in the direction of flow and the relative motion between the sampling platform and fine structure element. Fine structure lenses are considerably longer parallel to the ice edge with similarity in temperature structure noted over distances of 80 and 100 km. Approved for public release; distribution is unlimited. supported in part by the Arctic Submarine Laboratory, Naval Ocean Systems Center, San Diego, California under Project Order Nos. 00610, 00002 and 00004. http://archive.org/details/temperaturefines00paqu